The Portrayal of Chinese Diaspora in Selected Novels by Amy Tan - Rajah Kumaran, Shangeetha (2004)
This research aims to examine and explore the treatment of the concept of diaspora in order to bring to light the portrayal of Chinese immigrants in the United States in selected novels by Amy Tan. The research objectives set out to explore the motherdaughter relationships and examine the cultural differences of Chinese diaspora. An analysis of three novels by Tan forms the basis of this research. This research enables readers to understand the difficulties faced by the Chinese diaspora in their everyday struggle of trying to adapt in a new culture. Furthermore, it gives an insight to the difference between two cultures – Chinese and American. A diasporic community not only have to struggle within them in order to adapt their way of thinking and culture to the new environment but also have to work hard to be accepted by the society that they are in.The findings indicate that in all of Amy Tan’s novels, it is evident that the Chineseborn mothers are trying to adapt and assimilate into the American culture while the American-born daughters are trying to accept their Chinese culture. Through this study, it is hoped that readers will be more aware of the challenges that a society is imposing on a diasporic community on the whole.